Multi-field information fusion-based analysis of the macroscopic and mesoscopic damage evolution and location identification of caving and water-conducting fracture zones for mining overburden - Jiangbo WEI; Shuangming WANG; Lang LIU; Baoning WEI; Deyu CHONG; Zhizhen LIU; Dongkui LI; Dengdeng ZHUANG; Jing ZHOU (Meitian dizhi yu kantan)
ObjectiveFor the coal mining areas in the middle reaches of the Yellow River, there is an urgent need to determine the failure characteristics of the mining overburden and the spatial structural evolution of caving and water-conducting fracture zones in the overburden, which is recognized as the major challenge in coal mining through gangue grouting filling in goaves. MethodsTo accurately identify the locations of the caving and water-conducting fracture zones in the mining overburden, this study investigated mining face 42205 in the Liangshuijing Coal Mine in northern Shaanxi Province. Using drilling data, this study constructed a numerical model of coal mining using the particle flow code method. Using this model, this study conducted a simulation analysis of the damage characteristics and patterns of the mining overburden, including microfracture development, the distribution of broken rock blocks, changes in vertical displacement, structural evolution of force chains, and the void fraction evolution. Furthermore, this study comprehensively determined the locations and morphologies of caving and water-conducting fracture zones in the overburden. Comparison with field measurements verified that the simulation results were accurate and reliable. Finally, this study proposed a method for accurately identifying the locations of the caving and water-conducting fracture zones using macroscopic and mesoscopic multi-field information fusion. Results and ConclusionsThe results indicate that the microfracture number in the mining overburden was positively correlated with the advancing distance of the mining face, presenting an exponential growth initially and then a linear growth. Under the condition of a bedrock/load layer thickness ratio approaching 1.0 and the presence of intact caving, fracture, and sagging zones in the mining overburden, the average length of the broken rock blocks in the overburden exhibited a nonlinear logarithmic growth with the rock layer height. As the mining face advanced, the height of the arch of strong force chains in the overburden increased first and then tended to be stable, and its span showed a variation trend consistent with that of the advancing speed of the mining face. The continuous increase in the load on the overburden led to the failure of the arch, which was the internal cause of the rock breaking-induced increase in the water-conducting fracture zone height. The strong force chains in the arch were characterized by a dense distribution vertically and a sparse distribution nearly horizontally from the bottom up. There was a negative correlation between the void fraction of the overburden and the rock layer height. Specifically, the average void fraction decreased gradually from 30% to about 10% in a nonlinear manner from the loose zone on both sides to the central compaction zone within the caving zone. The comprehensive identification based on multi-field information fusion revealed that the mining overburden had an average water-conducting fracture zone height of 69.00 m and an average caving zone height of 19.63 m, with an average fracture zone/mining height ratio of 19.71 and an average caving zone/mining height ratio of 5.61. Besides, the water-conducting fracture zone in the overburden displayed a regular trapezoid shape. The results of this study prove more accurate than those of traditional single-factor analysis. Therefore, in engineering applications, these results will provide a scientific basis for the accurate space calculation for the efficient filling of goaves with the slurry of gangue from caving zones in coal mining areas along the middle reaches of the Yellow River.